Promising method for determining the concentration of nano-sized diamond powders in water suspensions - Dorozinska, H.V.; Dorozinsky, G.V.; Maslov, V.P. (Functional Materials, 2018)
This work is devoted to investigation of water suspension of synthetic diamond powders with sizes of particles smaller than one micrometer, which is used in processing the materials of parts of optical and electronic devices. It has been shown the influence of various concentrations of diamond powders in distilled water on the response value of the sensor based on surface plasmon resonance (SPR) phenomenon. For comparison, there are performed investigations using the conductometric method. Experimental results show high sensitivity of the SPR method (840 ang. min · μg⁻¹·ml) to the low concentrations of the powder from 2 up to 50 μg/ml. The conductometric method is spurious. Experimental results are in a good agreement with the suspension model based on the approaches by Maxwell-Garnett and mathematical formalism of Jones scattering matrices (relative error of measurement results is no more than 5 %). The obtained results can be useful in applications for technological processes in enterprises of optical and electronic industry.